Islet cell encapsulation – Application in diabetes treatment. Issue 24 (December 2021) - Opara, Amoge; Jost, Alec; Dagogo-Jack, Sam; Opara, Emmanuel C
In this minireview, we briefly outline the hallmarks of diabetes, the distinction between type 1 and type 2 diabetes, the global incidence of diabetes, and its associated comorbidities. The main goal of the review is to highlight the great potential of encapsulated pancreatic islet transplantation to provide a cure for type 1 diabetes. Following a short overview of the different approaches to islet encapsulation, we provide a summary of the merits and demerits of each approach of the encapsulation technology. We then discuss various attempts to clinical translation with each model of encapsulation as well as the factors that have mitigated the full clinical realization of the promise of the encapsulation technology, the progress that has been made and the challenges that remain to be overcome. In particular, we pay significant attention to the emerging strategies to overcome these challenges. We believe that these strategies to enhance the performance of the encapsulated islet constructs discussed herein provide good platforms for additional work to achieve successful clinical translation of the encapsulated islet technology.